EFFECTIVENESS OF FERTILIZER APPLICATION ON SOYBEAN AREAS IN THE CONDITIONS OF THE NORTHERN STEPPE OF UKRAINE - Shepilova, T. P.; Petrenko, D. I.; Leshchenko, S. M.; Skrynnik, I. O.; Artemenko, D. Yu. (Scientific Progress & Innovations, 2021)
Considerable soybean spreading is stipulated by particularly valuable content of nutrients, high econom-ic efficiency of production, as well as the universal nature of using for food, feed and technical purposes. With the introduction of adapted early-maturing soybean varieties into production, the problem has arisen of ensuring guaranteed annual formation of high-quality seed yield. An important reserve for increasing soy-bean productivity is to improve fertilization conditions by applying micro-fertilizers. They make it possible to implement the potential productivity of modern intensive soybean varieties better, improve the development of root system, increase photosynthesis activity, and increase the number of nodules, beans and seeds. The research objective is to identify the influence of mineral fertilizers and seed treatment with micro-fertilizers on the productivity of the early-ripening Zolushka soybean variety in the conditions of the Northern Steppe of Ukraine. The task is to determine the effect of fertilizers on the plant height and weight, the number of nodules, and formation of structural elements of soybean yield. The research was conducted during 2018–2020 in the Northern Steppe of Ukraine. Weather conditions of the research period were characterized by uneven distribution of precipitation during soybean growing season. The results of the study show that using fertilizers has a positive effect on soybean productivity. The maximum height and weight of plants were ob-served at the application of N15P15K15 fertilizers and Nano-mineralis – 79.8 cm and 54.0 g, respectively. The using of micro-fertilizers had a positive effect on nodule formation; their number increased by 2.9–4.2 piec-es, or 8.0–11.5 %. At the background of mineral fertilizers, the number of nodules was smaller by an average of 6.9 %. The largest number of beans and seed weight were formed at using Nano-mineralis and N15P15K15 – 23.8 pieces and 4.17 g, which was more than the absolute control by 23.3 and 16.8 %, respectively. The application of N15P15K15 at sowing provided an increase in productivity of 0.11 t/ha (7.2 %). Using Reacom micro-fertilizer resulted in the yield increase by 0.09–0.10 t/ha (5.9–6.1 %). The highest productivity was ensured by applying mineral fertilizers and Nano-mineralis – 1.82 t/ha, where the productivity increase in comparison with the absolute control made 0.29 t/ha (19.0 %).